STUDENT ASSESSMENT ON FOOD SAFETY PRACTICES AMONG STALL OWNERS: A PROPOSED RECOMMENDATIONS FOR IMPROVEMENT (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The school canteen is a great place to encourage students to appreciate healthy eating. Schools need to be aware of safety procedures that protect learners from health risks. It poses a risk to students' health since school canteens often lack proper sanitation and hygiene facilities.   Poor nutritional and hygienic quality of meals, with low-quality raw materials and hygiene violations, are the main problems. Schools are urged to implement "Clean as You Go" (CLAYGO), as learners need to understand how they can contribute to keeping the school canteen clean for all parties involved: students, faculty, non-teaching staff, and food handlers. This research primarily focuses on developing a deeper understanding of food safety practices. We conducted a student assessment pertaining to food safety practices among stall owners. One hundred (100) randomly selected students from Bestlink College of the Philippines in Bulacan participated, and they were chosen using purposive random sampling. This study utilized a quantitative research design through a survey-type questionnaire to evaluate students who bought their meals at the school canteen. The results indicated a multidisciplinary approach to maintaining hygienic conditions throughout the school canteen. The study discussed the basic hygiene and preparation standards of the food served. It emphasizes how much the school canteen's food safety procedures need to be improved overall, with a focus on fundamental hygiene, correct food handling, and cleanliness standards. This research highlights the need for innovative and consistent regulations regarding food hygiene to protect consumers dining at school canteens. Our findings highlight significant food safety practices in school canteens in terms of nutritional value, food consistency, food safety, food handling, and food storage. Most of the respondents demonstrated a clear understanding of food safety. The study discussed how we should maintain food hygiene, be mindful of what food we should or should not eat, and understand basic food handling and storage. The study suggests reconducting a seminar for stall owners, providing insights on how to maintain safety in the food we consume, and utilizing an inspection checklist to bridge the gap between knowledge and practice in food safety, ultimately reducing the incidence of foodborne illnesses. It also suggests room for improvement in training and monitoring to enhance food safety practices.
Keywords: hygienic quality of meals; food safety practices; food consistency; nutritional value; food storage; claygo